Immunoreactivity and intoxication syndrome in patients with chronic viral hepatitis c - Lishnevska, Anastasiia; Chemych, Mykola; Chemych, Oksana; Chernetsky, Igor (Bangladesh Journal of Medical Science, 2023)
Method: Etiological, gender, age and laboratory characteristics of chronic viral hepatitis C (СVHC) were studied and analyzed. The distribution of patients depending on the virus genotype, the activity degree and the severity of liver fibrosis were found out. Indices of non-specific reactivity, endogenous intoxication and inflammation in the course of СVHC, their dependence on treatment were studied. Correlations between the values of non-specific reactivity, endogenous intoxication, inflammation and patients’ affiliation to the group of injecting drug users, the APRI score, the stage of liver fibrosis and the virus genotype were estimated. Significant increase in endogenous intoxication (LII, HII, ISS), non-specific immunoreactivity (IR, LMR, Ilymph, IA) and inflammation (ILG) at decrease in some endogenous intoxication indices (ISL, NRR) and inflammation (KI, ILESR) in patients with CHCV compared with healthy persons were established. Result: The decrease in endogenous intoxication indices (LII; HII; ISL; ISS; NRR) were observed during antiviral treatment. Such unambiguous reaction of non-specific immunoreactivity indices and inflammation indices were not observed: some of them increased (Ilymph, IA), some of them decreased (IR, NLR; ELR). KI decreased during the treatment, but ILG increased. Direct correlation between patients’ affiliation to a group of injecting drug patients and the values of HII, NRR (p<0.05), between the APRI score and Ilymph level (p<0.05) was identified. Conclusion: No correlation between the indices values and fibrosis severity (according to METAVIR) and virus genotype was found. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 508-514